ASSISTING STUDENTS WITH FINANCIAL DIFFICULTIES ALWAYS A PRIORITY OF THE UNIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 9 January 2016 In response to the article reported in The Star on the efforts to assist in providing free meals to students who come from poor families, Universiti Sains Malaysia (USM) would like to emphasise that this has been a longstanding practice by the university.